Miniaturised broth microdilution for simplified antibiotic susceptibility testing of Gram negative clinical isolates using microcapillary devices. Issue 15 (8th July 2022) - Needs, Sarah H.; Saiprom, Natnaree; Rafaque, Zara; Imtiaz, Wajiha; Chantratita, Narisara; Runcharoen, Chakkaphan; Thammachote, Jeeranan; Anun, Suthatip; Peacock, Sharon J.; Ray, Partha; Andrews, Simon; Edwards, Alexander D.
Abstract : Miniaturised antibiotic susceptibility testing: 100 times smaller microcapillary broth microdilution gives equivalent result to standard microplate broth microdilution. Abstract : Antibiotic resistance is a major global challenge. Although microfluidic antibiotic susceptibility tests (AST) offer great potential for rapid and portable testing to inform correct antibiotic selection, the impact of miniaturisation on broth microdilution (BMD) is not fully understood. We developed a 10-plex microcapillary based broth microdilution using resazurin as a colorimetric indicator for bacterial growth. Each capillary had a 1 microlitre capillary volume, 100 times smaller than microplate broth microdilution. The microcapillary BMD was compared to an in-house standard microplate AST and commercial Vitek 2 system. When tested with 25 uropathogenic isolates (20 Escherichia coli and 5 Klebsiella pneumoniae ) and 2 reference E. coli, these devices gave 96.1% (441/459 isolate/antibiotic combinations) categorical agreement, across 17 therapeutically beneficial antibiotics, compared to in-house microplate BMD with resazurin. A further 99 (50 E. coli and 49 K. pneumoniae ) clinical isolates were tested against 10 antibiotics and showed 92.3% categorical agreement (914/990 isolate/antibiotic combinations) compared to the Vitek 2 measurements. These microcapillary tests showed excellent analytical agreement with existing AST methods. Furthermore, the small size and simple colour change can be recorded using a smartphone camera or it is feasible to follow growth kinetics using very simple, low-cost readers. The test strips used here are produced in large batches, allowing hundreds of multiplex tests to be made and tested rapidly. Demonstrating performance of miniaturised broth microdilution with clinical isolates paves the way for wider use of microfluidic AST.